The Influence of Reward Systems, Job Satisfaction, and Salary on Employee Engagement among Employees of PT. Deli Jaya Samudera Medan - Victor Victor; Syifa Latifah; Ferry Hidayat (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study aims to analyze the effect of Reward System, Job Satisfaction, and Salary on Employee engagement  at PT. Deli Jaya Samudera Medan. This research used a quantitative approach with a population of 30 employees. The sampling technique used in this study was saturated sampling, in which all members of the population were selected as the research sample. The results of the study indicate that Reward System, Job Satisfaction, and Salary partially have a positive and significant effect on Employee engagement . A good Reward System can increase employees’ enthusiasm and engagement at work. High job satisfaction makes employees feel comfortable, loyal, and committed to the company. In addition, appropriate salaries can improve employees’ motivation and sense of responsibility in carrying out their work. Simultaneously, the three variables have a significant effect on Employee engagement, as evidenced by the Fcount value of 10.543, which is greater than the Ftable value of 2.92, with a significance level of 0.001 < 0.05. This means that Reward System, Job Satisfaction, and Salary together have a positive and significant effect on Employee engagement  at PT. Deli Jaya Samudera Medan. The coefficient of determination (R Square) value of 0.549 or 54.9% indicates that the variables of Reward System, Job Satisfaction, and Salary are able to explain the effect on Employee engagement  by 54.9%, while the remaining 45.1% is influenced by other variables outside this study, such as work environment, work motivation, leadership style, organizational culture, and other factors.